Pinealectomy alters IFN-Î³ and IL-10 levels in primary thymocyte culture of rats - Sahin, Zafer; Sandal, Suleyman; Yilmaz, Bayram; Bulmus, Ozgur; Ozdemir, Gokcen; Kutlu, Selim; Godekmerdan, Ahmet; Kelestimur, Haluk (Cellular and Molecular Biology, 2018)
Melatonin, produced mainly by the pineal gland, has an immunomodulatory role. However, the effects of the pineal gland and/or melatonin on thymus cytokine levels such as interferon-gamma (IFN-Î³), interleukin (IL)-4, and IL-10 are not well known. Twenty-one male Wistar rats (220-250 gr) were randomly divided into three groups (n=7): intact control, sham, and pinealectomy. Primary thymocyte cultures were prepared from each group and dispensed into well plates as Control, DMSO (or vehicle), Sham-pinealectomy, Pinealectomy, Pinealectomy+10µM melatonin, and Pinealectomy+100µM melatonin. IFN-Î³, IL-4, and IL-10 concentrations were measured in the thymocytes (as nonstimulated and Concanavalin A-stimulated) after 24 h. IFN-Î³ levels significantly increased and IL-10 levels significantly decreased in both media prepared from pinealectomized rats. There was no significant difference between the groups in terms of IL-4. In the pinealectomy+10µM melatonin group, IFN-Î³ and IL-10 levels did not differ from the pinealectomy group. However, the dose of 100µM melatonin caused a decrease in levels of IFN-Î³ in both thymocyte media and an increase in the concentration of IL-10 in Concanavalin A-stimulated thymocytes. In conclusion, pineal gland and/or melatonin affect IFN-Î³ and IL-10 levels in the thymus gland.